Country characteristics and the choice of the exchange rate regime: are mini-skirts followed by maxis? - Seppo Honkapohja; Pentti Pikkarainen (Bank of Finland, 1992)
The paper studies empirically how different country characteristics are associated with the choice of a country's exchange rate regime. The sample consists of 140 economies, both developing and industrialized nations. When countries are classified according to their current exchange rate arrangements, we observe that small countries with low diversification of exports are the most likely candidates to peg their exchange rates. Other country characteristics, like the level of development, openness of the real or financial sector, geographical diversification of exports, and fluctuations in the terms of trade, have hardly any power in explaining the choice of a country's exchange rate system. Somewhat surprisingly it is developing countries which have moved towards more flexible exchange rate practices during the last 10 years. Meanwhile countries with well diversified exports have adopted more rigid exchange rate arrangements. In the light of our evidence and "conventional wisdom" the emerging monetary unification among the EC countries is somewhat peculiar. On the one hand, the EMS countries are quite large and rich, they are well integrated financially, and their trade is well diversified. According to "conventional wisdom" economies of this type tend to be floaters rather than restrict fluctuations in exchange rates. On the other hand, the EMS economies are very open in terms of the real sector, and terms of trade fluctuations have been very low in the EMS countries. Traditionally, such economies are considered to restrict fluctuations in exchange rates. The estimating models predict the following pressures. Firstly, Italy, Spain, and the United Kingdom should have floating exchange rates. Secondly, Israel, New Zealand, and Switzerland should adopt more rigid practices than their current ones. Thirdly, Finland should be in the group of limited flexibility (like the EMS) rather than peg to a basket or float.
URN:NBN:fi:bof-201908081375
Keywords: 330